1996
DOI: 10.1016/s0092-8674(00)81069-7
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast Growth Factor Receptor 3 Is a Negative Regulator of Bone Growth

Abstract: Endochondral ossification is a major mode of bone that occurs as chondrocytes undergo proliferation, hypertrophy, cell death, and osteoblastic replacement. We have identified a role for fibroblast growth factor receptor 3 (FGFR-3) in this process by disrupting the murine Fgfr-3 gene to produce severe and progressive bone dysplasia with enhanced and prolonged endochondral bone growth. This growth is accompanied by expansion of proliferating and hypertrophic chondrocytes within the cartilaginous growth plate. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
711
1
3

Year Published

1998
1998
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,000 publications
(736 citation statements)
references
References 42 publications
21
711
1
3
Order By: Relevance
“…We have shown that Cyr61 can directly promote the chondrogenic di erentiation of mouse limb mesenchymal cells in micromass cultures (Wong et al, 1998). Given the role of FGF signaling mechanism in development of the embryonic skeleton (Niu et al, 1997;Muenke and Schell, 1995;Ishigaki et al, 1997;Deng et al, 1997), it remains possible that CYR61 may interact and cooperate with FGF function in this organ system.…”
Section: Discussionmentioning
confidence: 91%
“…We have shown that Cyr61 can directly promote the chondrogenic di erentiation of mouse limb mesenchymal cells in micromass cultures (Wong et al, 1998). Given the role of FGF signaling mechanism in development of the embryonic skeleton (Niu et al, 1997;Muenke and Schell, 1995;Ishigaki et al, 1997;Deng et al, 1997), it remains possible that CYR61 may interact and cooperate with FGF function in this organ system.…”
Section: Discussionmentioning
confidence: 91%
“…Homologous recombination in ES cells and generation of germline chimeras TC1 ES cells (Deng et al, 1996) were transfected with NotI digested pBrca1neo and selected with G418 and FIAU. The culture, electroporation, and selection of TC1 cells was carried out as described .…”
Section: Targeting Vectormentioning
confidence: 99%
“…The isolation, culture, and injection of ES cells were performed as described previously (Deng et al, 1996). For ␤-galactosidase staining, embryos were washed in PBS with 2 mM MgCl 2 , 0.01% Nadeoxycholate, 0.02% NP-40 for 30 -60 min, then stained in X-gal overnight at 37°C as described (Mansour et al, 1993).…”
Section: Fgfr2 ⌬Iii/⌬iii Es Cell Isolation and ␤-Galactosidase Stainingmentioning
confidence: 99%
“…Gene targeting in mice shows that Fgfr1-null embryos die before E9.5 displaying severe growth retardation, cell migration defects, and defective mesodermal structures (Ciruna, 1997;Deng et al, 1994Deng et al, , 1996Yamada et al, 1994). Fgfr1␣-isoform knock-outs die at E9.5-12.5 due to the failure of axial mesoderm cell migration toward the posterior portions of the embryos.…”
Section: Introductionmentioning
confidence: 99%